2011
DOI: 10.1007/s10384-011-0009-3
|View full text |Cite
|
Sign up to set email alerts
|

Residual anterior chamber angle closure in narrow-angle eyes following laser peripheral iridotomy: anterior segment optical coherence tomography quantitative study

Abstract: Overall, ACA parameters changed significantly after LPI; however, when assessed by AS-OCT, ACA remained unchanged in some narrow-angle eyes despite LPI. Our findings suggest that multiple causes other than pupillary block may contribute to narrow-angle closure following LPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Hence, some studies have reported that LPI might not be effective in treating all narrow angles. [8][9][10][11][12] Therefore, other pathogenic mechanisms, such as forward movement of the lens or a plateau iris configuration, have also been suggested to contribute to PAC. [13][14][15][16] Those outcomes suggest that PAC is not a single disease entity caused by single mechanism and thus may be classifiable into several categories with differing features.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, some studies have reported that LPI might not be effective in treating all narrow angles. [8][9][10][11][12] Therefore, other pathogenic mechanisms, such as forward movement of the lens or a plateau iris configuration, have also been suggested to contribute to PAC. [13][14][15][16] Those outcomes suggest that PAC is not a single disease entity caused by single mechanism and thus may be classifiable into several categories with differing features.…”
Section: Purposementioning
confidence: 99%
“…Image acquisition procedure and analysis method are described in detail elsewhere. 12,19,20 ACD was defined as the distance from the corneal endothelium to the anterior surface of the lens. The scleral spur was defined as the point at which a change in curvature of the inner surface of the angle wall became apparent, and often presented as an inward protrusion of the sclera.…”
Section: As Oct Imagingmentioning
confidence: 99%
“…1,2 However, in previous studies, the AC angles of some ACG eyes that underwent LPI remained closed. [3][4][5] Furthermore, some eyes that underwent LPI showed progression of peripheral anterior synechiae (PAS). [6][7][8] These observations raise the questions whether pupillary block is the only mechanism of ACG, and whether LPI is suitable for treating all types of ACG.…”
mentioning
confidence: 99%
“…13,14 Recent studies using AS OCT showed that LPI substantially increased the AC angle width in ACG eyes. 5,[15][16][17][18][19] Lee et al found that approximately two-thirds of patients with a narrow angle showed opening of the AC angle after LPI. 5 However, these results were obtained early post-LPI, with post-LPI imaging performed at 1 week to 1 month.…”
mentioning
confidence: 99%
See 1 more Smart Citation